PELAKSANAAN SALAT DUHA PADA ANAK USIA 4-5 TAHUN DI TK AL – ADABIY PONTIANAK - Irmayani, Sri; Syukri, M.; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the implementation of salat duha children aged 4-5 years in kindergarten Al-Adabiy Pontianak. This research uses descriptive method with qualitative approach. The data sources of this research are teachers and class A students and data from observation guides, interview guides, documentation and field notes. The results of this study indicate the planning that teachers do in implementing salat duha in children have been categorized either because the teacher has set goals to be achieved, the media images or props, facilities and infrastructure, the child's assessment sheet and time, steps of prayer implementation duha children are also quite good because in accordance with the goals and strategies that teachers have made and children are also enthusiastic or enthusiastic in carrying out praying prayer duha, support factors in the implementation of prayers duha has become a role model in the implementation, inhibiting the implementation of salat duha also resolved well because of solutions contained in the implementation of prayer duha so as to make the child become happy carry out habituation prayer duha. Keywords: Duha Prayer, Habituation